Understanding the impact of zakat and waqf as economic development of the community in rural areas - Yusroni, Nanang; Chadhiq, Umar (International research journal of management, IT and social sciences, 2021)
This study discusses the understanding of the impact of Zakat and Waqf spending as part of the government's efforts with the community to develop the economy of the poor in rural areas. We use secondary data in answering the research questions from some zakat and people's economy publications from international publications, including journal articles, books, proceedings, and other data on internet sites that discuss the importance of zakat in the Islamic economy. After we found the data, we analyzed it using a phenomenological approach, a way to explore as much data as possible to solve problems with valid and reliable data findings. We choose the publication of data published ten years ago to be genuinely accurate and updated. Based on the findings and discussion data, we can summarize that zakat and the economy are two things that influence each other. As a result, the Islamic economy cannot be separated from Zakat and Waqf, which are potential instruments in improving the economy. With the existing economic problems, zakat and waqf can be an effective solution to overcome financial issues faced by the ummah.